Tinjuan Prinsip-Prinsip Visual Pada Komik “Guild” Karya Irfan Rianto - Muhammad Choir Affandi Adjie Rangkuti; Onggal Sihite (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
Comic "Guild" is a comic that has a Japanese drawing style, namely Manga and applies visual principles that should be used as study material to study visual principles about comics. This study aims to identify and review the visual comics of "Guild" in terms of these principles. the principle of visual emphasis according to MS Gumelar. The population in this study is 15 pages in chapter 1 of the comic "Guild". This type of research uses qualitative research methods with documentation data collection techniques and literature study. Primary data is in the form of visual comic “Guild” chapter 1 by Irfan Rianto, data collection in this research is through literature study, observation, data processing, data analysis techniques, generalizations and instruments. Then the data that has been collected is triangulated to strengthen the credibility of the research results. From the results of the study it was concluded that the comic "Guild" had applied the principles of visual emphasis according to the MS Gumelar guidelines, although in its application there were still five pages that still had shortcomings so that it looked not optimal and consistent.